Membangun Pemahaman Keagamaan Generasi Milenial Melalui Metode Diskusi: Analisis Podcast Ustadz Hanan Attaki di Youtube - Alvina Nurdianti; Amin Fauzi (PKP Pusat Jurnal LPPM IAi Nasional Laaroiba, 2024)
The aim of this research is to examine the messages of goodness and religion conveyed through discussion methods by contemporary preachers among young millennials. Specifically, this research aims to analyze the method of Ustadz Hanan Attaki's preaching podcast to millennials on Ustadz Hanan Attaki's YouTube channel. This research uses qualitative research methods with a library research or literature study approach. The research results show that; The content of the da'wah message conveyed by Ustadz Hanan Attaki on social media through his podcast is in the form of encouragement, advice, reprimand, which is packaged in video form and equipped with a glossary that can be edited so that the millennial generation can easily accept and understand it. The method of delivering Ustadz Hanan Attaki's preaching is through distinctive audio and visual styles according to certain issues and themes which are discussed dialogically each week. Likewise, the title of the da'wah content attracts the interest of the motivated young millennial generation.